Peradaban Islam Melayu - Jajat Burhanudin (Studia Islamika, 1998)
"Civilization", the term employed as the main title of the book under review, is of spesific significance to us here. The term has appeared only in recent scholarly works on Southeast Asian Islam, especially those written by oreintalists.This paper is a review of the book Mohd. Taib Osman, (ed.), Islamic Civilization in the Malay World (Kuala Lumpur and Istanbul: Language and Library Board and the Research Centre for Islamic History, Art, and Culture, 1997).DOI: 10.15408/sdi.v5i1.763